2023
DOI: 10.1186/s13054-023-04399-5
|View full text |Cite
|
Sign up to set email alerts
|

The physiologic response to epinephrine and pediatric cardiopulmonary resuscitation outcomes

Abstract: Background Epinephrine is provided during cardiopulmonary resuscitation (CPR) to increase systemic vascular resistance and generate higher diastolic blood pressure (DBP) to improve coronary perfusion and attain return of spontaneous circulation (ROSC). The DBP response to epinephrine during pediatric CPR and its association with outcomes have not been well described. Thus, the objective of this study was to measure the association between change in DBP after epinephrine administration during CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“… 15 , 16 Translational and clinical studies have established wide variability in DBP responsiveness to epinephrine during CPR, including no response in many patients. 23 , 24 Our pharmacodynamics data during CPR suggested that the present epinephrine dosing and dosing intervals might not be optimal. New strategies might be necessary for optimal epinephrine administration during CPR.…”
Section: Discussionmentioning
confidence: 90%
“… 15 , 16 Translational and clinical studies have established wide variability in DBP responsiveness to epinephrine during CPR, including no response in many patients. 23 , 24 Our pharmacodynamics data during CPR suggested that the present epinephrine dosing and dosing intervals might not be optimal. New strategies might be necessary for optimal epinephrine administration during CPR.…”
Section: Discussionmentioning
confidence: 90%
“…Intra-arrest invasively measured blood pressure data were prospectively collected and analyzed as a component of the ICU-RESUS trial [ 18 , 19 , 25 , 29 ]. We evaluated the association between intra-arrest mean DBP targets and post-arrest study SBP and DBP thresholds at 0–6 h post-arrest using Poisson regression with robust error estimates, controlling for illness category and pre-arrest hypotension.…”
Section: Methodsmentioning
confidence: 99%
“…The data collection and physiological waveform analysis methods of the parent trial, and subsequent secondary studies, have been previously published. [13][14][15] In brief, trained research coordinators collected standardized cardiopulmonary arrest data elements, 16 CPR quality mechanics data (eg, compression depth and rate), and physiological bedside monitor data (eg, electrocardiogram, invasive arterial line, and quantitative capnography) for index CPR events (ie, the first event associated with the hospitalization). Baseline Pediatric Cerebral Performance Category 17,18 and Functional Status Scale 19 scores were based on the patient's preadmission baseline and calculated on the basis of documentation review.…”
Section: Data Collectionmentioning
confidence: 99%